Construction of a Porous Metal–Organic Framework with a High Density of Open Cr Sites for Record N2/O2 Separation. Issue 37 (4th August 2021) - Zhang, Feifei; Shang, Hua; Wang, Li; Wang, Yong; Yang, Jiangfeng; Xia, Yuanhua; Li, Hao; Li, Libo; Li, Jinping
Abstract: The removal of low concentration N2 is of great significance and challenging in the industrial production of high‐purity O2 . Herein, a chromium‐based metal–organic framework, namely, TYUT‐96Cr, is reported, which has an unprecedented N2 capture capacity of 37.46 cm 3 cm −3 and N2 /O2 (5:95, v/v) selectivity up to 26.95 (298 K and 1 bar), thus setting new benchmarks for all reported metal–organic frameworks and commercially used ones (Li‐LSX and 13X). Breakthrough experiments reveal that N2 can be directly extracted from various N2 /O2 (79:21, 50:50, 5:95, and 1:99, v/v) mixtures by this material, affording a record‐high O2 ‐production scale with 99.99% purity. Density functional theory calculations and in situ infrared spectroscopy studies demonstrate that the high‐density open Cr (III) sites in TYUT‐96Cr can behave as effective Lewis acidic sites, thus resulting in a strong affinity toward N2 . The high N2 adsorption selectivity, exceptional separation performance, and ultrahigh structural stability render this porous material with great potential for this important industrial application. Abstract : A N2 ‐selective metal–organic framework material TYUT‐96Cr, with dual open Cr (III) sites, record‐high N2 capture capacity, and N2 /O2 selectivity is developed, showing the highest separation performance, far beyond the current adsorbents. Importantly, this material displays ultrahigh structural stability under water, acid/base, and humidity conditions, being practically useful for O2 separation and purification in industry.